Assessing Retention of Women Enrolled in Prevention of Mother-To-Child Transmission of HIV Programme at the Ho Municipal Hospital - Folitse, I. (University of Ghana, 2017)
Background: Prevention of mother-to-child transmission of HIV (PMTCT) is delivered in stages (or cascades) and high level of retention at each cascade step by mother and later by mother-infant pairs is required to eliminate maternal transmission of HIV which occurs through pregnancy, childbirth and breastfeeding. Reasons for low rates of retention in Ghana are not well understood though HIV sentinel sites situated across the country serve as good resource for collecting data for generating such knowledge. The aims of this study were to determine retention rates at each stage of tile PMTCT cascade and explore patient and provider- level factors affecting retention at the Ho Municipal Hospital. Methods: Retrospective data was collected from folders and electronic records of 69 women who were enrolled into PMTCT from January 20 14 to December 2015. Data was entered into a PMTCT Cascade Analysis Tool and retention rates at different stages of the cascade was calculated. In-depth interviews were conducted for twelve mothers and seven carefully selected frontline PMTCT care providers. Patient-level and provider-level factors were manually extracted and Coded from transcribed recorded conversation. Findings/Results: Twelve-month postpartum retention was 66.7%. The highest drop-off along the cascade was found at the ' first at-risk child visit' for which 20 out of 52 babies were not brought for early infant diagnosis (EID). Provider-level factors identified as determinants for retention included counselling support, assurance of anonymity, clinic location and supportive and understanding team. Patient- level factors that emerged were desired quality life, social support and acceptance, stigma, and partner influences. Conclusion: Retention in PMTCT at the Ho Municipal Hospital was lower compared to reviewed literature from other resource constraint locations. Good counselling support, assurance or confidentiality. desired treatment outcome and privacy of clinic location are some of the reasons shown to affect retention at this site.
MSc. Public Health
Keywords: HIV; Mother-to-child transmission; Ho Municipal Hospital; Ghana; Prevention of HIV